2007
DOI: 10.1007/s11661-007-9270-y
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Grain-Scale Stresses and Modeling of Tensile Deformation in a ZIRCALOY-4 Weldment

Abstract: Tensile tests and neutron diffraction measurements of the residual elastic strain response to applied uniaxial stress have been made on samples taken from a ZIRCALOY-4 (Zr-4) weld in the as-welded condition. The samples were taken from the parent plate, and the weld metal and time-of-flight neutron diffraction measurements were made parallel and perpendicular to the applied stress direction, which corresponds to the weld direction and the transverse direction in the plane of the plate. Measurements were made o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…MacEwen et al [1989] have shown that the Taylor-type approach does not work well for the prediction of residual grain-interaction stresses in zirconium alloys. On the other hand, it has been demonstrated that the evolution of internal strains and stresses in HCP polycrystalline AZ31 and Zircaloy-4 can be predicted with the aid of the elastic-plastic self-consistent model [see Agnew et al, 2006;Carr et al, 2007]. It is now generally accepted that a self-consistent approach is more suitable than the full constraint Taylor approach for the constitutive modeling of HCP polycrystals.…”
Section: Introductionmentioning
confidence: 99%
“…MacEwen et al [1989] have shown that the Taylor-type approach does not work well for the prediction of residual grain-interaction stresses in zirconium alloys. On the other hand, it has been demonstrated that the evolution of internal strains and stresses in HCP polycrystalline AZ31 and Zircaloy-4 can be predicted with the aid of the elastic-plastic self-consistent model [see Agnew et al, 2006;Carr et al, 2007]. It is now generally accepted that a self-consistent approach is more suitable than the full constraint Taylor approach for the constitutive modeling of HCP polycrystals.…”
Section: Introductionmentioning
confidence: 99%
“…Kaschne et al (2000) found that the compressive-yield responses of high and low-purity Zr depend on the loading orientation relative to the c-axis of the hexagonal closed packed cell. Carr et al (2007) studied the variations in residual lattice strains parallel and perpendicular to the applied stress with neutron diffraction measurements on a variety of crystallographic reflections. A set of macrographs of the ZR4-EBW-W1 post-tensile specimen are shown in Figure 11.…”
Section: Tensile Testmentioning
confidence: 99%
“…The penetration of neutrons into zirconium allows measurement of lattice strains to evaluate the residual stresses as a function of location as is needed to determine stress profiles across a weld. In an exhaustive study, Carr et al determined the residual stresses [90,91] and the strain evolution during loading of the weld in a Zircaloy-4 weld using time-of-flight neutron diffraction from the measured lattice strains and the texture of the material [92]. Figure 7 shows some results of these studies.…”
Section: Residual Stressmentioning
confidence: 99%